1995
DOI: 10.1111/j.1600-0447.1995.tb09762.x
|View full text |Cite
|
Sign up to set email alerts
|

Mortality among patients in psychiatric hospitals in Germany

Abstract: Data from 7 psychiatric hospitals with defined catchment areas were analyzed; 14,195 episodes of treatment in acute psychiatry wards were recorded within 30 months. During their stay in hospital 196 patients died, 174 from natural causes and 22 by suicide, compared to the expected 32 deaths. Standardized mortality ratios (SMRs) were calculated for the different diagnostic and age groups, mortality risk being highest in organic mental disorder (SMR 7.55), followed by functional psychoses (SMR 4.55) and the "oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
22
1
5

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 30 publications
10
22
1
5
Order By: Relevance
“…The elderly have an increased risk of natural deaths but not of deaths from unnatural causes. This is largely in agreement with other hospital-based mortality studies (1)(2)(3)(4)(5)8,9,13,14), even though there are differences with regard to the elderly suicide risk (1,3).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The elderly have an increased risk of natural deaths but not of deaths from unnatural causes. This is largely in agreement with other hospital-based mortality studies (1)(2)(3)(4)(5)8,9,13,14), even though there are differences with regard to the elderly suicide risk (1,3).…”
Section: Discussionsupporting
confidence: 88%
“…Old mortality studies, as referred by Babigian & Odoroff (1 l ) , showed much higher mortality, but these studies concerned inpatients of mental state hospitals, and the excess mortality is thought to be due to conditions peculiar to the hospital facilities. More recent studies show surprisingly good agreement about the non-findings (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16), even though the studies have been conducted on in-or out-patients, or both, and there are some differences in methods (1,12,13). Most of these studies indicate that males have a higher death rate than females, but females have a higher standard mortality ratio ( S M R ) when compared with the general population.…”
mentioning
confidence: 79%
“…The need for a thorough medical examination at admission in psychiatric wards has been stressed by several authors (35,39,40). Deficits in quality of medical care seemed to explain a substantial portion of the excess mortality experienced by patients with mental disorders, as showed by Druss et al (17) in those patients who experienced myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…Die notfallpsychiatrische behandlung suizidgefährdeter Patienten in Kliniken für Psychiatrie und Psychotherapie ist dabei traditioneller auftrag. Dass aber auch unter besten rahmenbedingungen von Diagnostik, Pflege und Therapie, Fürsorge, Kommunikation und Kontrolle immer wieder Patienten dennoch durch Selbsttötung versterben oder auch schwere Suizidversuche unter stationären psychiatrisch-psychotherapeutischen behandlungsbedingungen stattfinden, zeigt, dass es eine omnipotente Suizidprävention auch im psychiatrischen Fachkrankenhaus nicht gibt -und im Übrigen auch nie gegeben hat [1][2][3][4][5][6][7][8]. nach der Metaanalyse von bertolote et al [7] weisen 98 % aller Suizidenten eine psychiatrische Diagnose auf.…”
Section: Einleitung - Kurzer Historischer Rückblickunclassified